Searching for New Physics with DarkLight at the ARIEL Electron-Linac. Issue 1 (1st December 2022) - ,; Cline, E; Corliss, R; Bernauer, J C; Alarcon, R; Baartman, R; Benson, S; Bessuille, J; Ciarniello, D; Christopher, A; Colon, A; Deconinck, W; et al.
Abstract: The search for a dark photon holds considerable interest in the physics community. Such a force carrier would begin to illuminate the dark sector. Many experiments have searched for such a particle, but so far it has proven elusive. In recent years the concept of a low mass dark photon has gained popularity in the physics community. Of particular recent interest is the 8 Be and 4 He anomaly, which could be explained by a new fifth force carrier with a mass of 17 MeV/ c 2 . The proposed Darklight experiment would search for this potential low mass force carrier at ARIEL in the 10-20 MeV/ c 2 e + e − invariant mass range. This proceeding will focus on the experimental design and physics case of the Darklight experiment.